Seismic Shot Point Navigation Data from the Norwegian Margin and the Norwegian-Greenland Sea acquired during the R/V Robert D. Conrad expedition RC2114 (1978) ... - Diebold, John; Buhl, Peter; Stoffa, Paul; Talwani, Manik (Interdisciplinary Earth Data Alliance (IEDA), 2006)
This data set was acquired with the LDEO Multi-Channel Seismic system during R/V Robert D. Conrad expedition RC2114 conducted in 1978 (Chief Scientist: Dr. John Diebold; Investigator: Dr. John Diebold, Dr. Peter Buhl, Dr. Paul Stoffa, and Dr. Manik Talwani). These data files are of ASCII format and include Seismic Shot Point Navigation data that provide the primary seismic navigation source for this cruise. Data were acquired as part of the project: Norwegian Sea - The Application of Multichannel Seismic Reflection/Refraction Techniques to Define the Crustal Structure of the Norwegian Margin and the Norwegian-Greenland Sea, and funding was provided by NSF grant: DPP78-05733. ...